A method for simulating crack growth behavior in heterogeneous asphalt mixtures
By establishing a finite element model of indirect tensile cracking test of heterogeneous asphalt mixture in finite element software, the impact of transition zone and void ratio from the mesoporous structural interface on cracking behavior is simulated, and the problem of difficult to capture the crack formation process in the prior art is solved, and a detailed analysis and performance evaluation of the crack expansion behavior of asphalt mixture is achieved.
Patent Information
- Application Number
- CN202411757748.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The prior art is difficult to effectively capture the formation process of heterogeneous asphalt mixture cracks, and the lack of internal meticulous and microscopic mechanisms has hindered the in-depth study of the crack expansion behavior and cracking mechanism of asphalt mixture.
By establishing a finite element model of indirect tensile cracking test of heterogeneous asphalt mixture in finite element software, the effect of transition zone and void ratio from the mesoporous structural interface on cracking behavior is simulated. The method includes screening test to obtain aggregate particle size distribution, determine the optimal asphalt usage, prepare different types of test pieces for testing, and use the test results for parameter calibration and simulation of finite element models.
Detailed visualization and quantitative analysis of the initiation, expansion and penetration of asphalt mixture cracks is realized, revealing the impact of interface transition zone and void ratio on cracking behavior, providing more accurate data support for cracking mechanism and performance evaluation of asphalt mixture.
Smart Images

Figure CN119252397B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of civil engineering, and in particular to a method for simulating crack expansion behavior of heterogeneous asphalt mixture. Background Art
[0002] The crack propagation behavior of heterogeneous asphalt mixtures is an important research topic in the field of road engineering. Asphalt pavement is one of the main forms of roads, and its cracking problem will seriously affect the service life and driving safety of the road. Heterogeneous asphalt mixtures are composed of multiple components such as coarse aggregate, asphalt mortar and voids. The generation of cracks in heterogeneous asphalt mixtures usually originates from changes in the microscopic characteristics of the structure.
[0003] A method for simulating the cracking behavior of asphalt mixture taking into account the random heterogeneity of binder, with publication number CN115060749B, comprises the following steps; step one: preparation of asphalt mixture specimens; step two: CT scanning of specimens; step three: obtaining the microscopic characteristics of asphalt mixture; step four: extracting different binder thicknesses; step five: importing binders and aggregates of different thicknesses into finite element software; step six: obtaining model parameters of binders of different thicknesses; step seven: determining other model parameters of asphalt mixture; step eight: inserting cohesive units in batches and regions; step nine: model analysis, by considering the random heterogeneity of binder distribution, and according to the failure modes of different binder thicknesses, the adhesion CZM, cohesive CZM, adhesion-cohesive CZM are determined and cohesive units are inserted, and then the CZM parameters of binders of different thicknesses are assigned to the corresponding adhesion CZM, cohesive CZM and adhesion-cohesive CZM to simulate the cracking behavior of asphalt mixture.
[0004] Asphalt mixture is a heterogeneous material composed of coarse aggregate, asphalt mortar and voids. The generation of cracks in it usually originates from the changes in the microscopic characteristics of the structure. Existing traditional mechanical properties tests cannot effectively capture the formation process of asphalt mixture cracks, and lack consideration of internal mesoscopic and microscopic mechanisms, which hinders in-depth research on the crack propagation behavior and cracking mechanism of asphalt mixture. Summary of the invention
[0005] In view of this, the present invention proposes a method for simulating the crack propagation behavior of heterogeneous asphalt mixtures. By establishing a finite element model for the indirect tensile cracking test of asphalt mixtures, it is possible to analyze the effects of the interface transition zone and void ratio on the cracking behavior of asphalt mixtures from the internal microstructure.
[0006] The technical solution of the present invention is implemented as follows: The present invention provides a method for simulating the crack propagation behavior of a heterogeneous asphalt mixture, comprising the following steps:
[0007] S1, use screening test to obtain the aggregate particle size distribution, and determine the aggregate gradation based on the screening results;
[0008] S2, determining the type of asphalt mixture, conducting tests according to aggregate gradation and the type of asphalt mixture to obtain an optimal asphalt dosage, wherein the type of asphalt mixture includes asphalt, aggregate and mineral powder;
[0009] S3, preparing indirect tensile test pieces of asphalt mixture and asphalt mortar, dynamic modulus test pieces of asphalt mortar and aggregate-asphalt-aggregate interface tensile test pieces, performing corresponding indoor test tests on each test piece, and obtaining corresponding test results;
[0010] S4, converting the three-dimensional gradation of the aggregate gradation of the asphalt mixture into a two-dimensional gradation, randomly generating an indirect tensile test finite element specimen of the asphalt mixture with irregular aggregates in a two-dimensional dimension according to the two-dimensional gradation, and performing a finite element simulation to obtain a finite element simulation result;
[0011] S5, comparing the finite element simulation results with the corresponding test results to verify whether the finite element simulation results are accurate, and outputting cracking images of crack initiation, crack propagation and crack penetration of the asphalt mixture indirect tensile test numerical specimen;
[0012] S6, establish indirect tensile test finite element specimens of asphalt mortar-circular and elliptical aggregate interface transition zones, and perform finite element simulations to output the crack propagation trajectory and the curve of total crack length changing with finite element field output time when the three types of indirect tensile test finite element specimens of interface transition zones completely fail, and obtain the influence of interface transition zone differences on crack propagation behavior;
[0013] S7, establish indirect tensile test finite element specimens with different void ratios, perform finite element simulation, output load-displacement and energy-displacement curves of the indirect tensile test finite element specimens with different void ratios, and obtain the influence of void ratio change on cracking behavior.
[0014] On the basis of the above technical solution, preferably, the step S1 of obtaining the particle size distribution of aggregate by a screening test and determining the aggregate gradation according to the screening result comprises the following sub-steps:
[0015] S11, placing the aggregate into an oven, drying to constant weight, and selecting the mesh size of the sieve according to the aggregate size;
[0016] S12, placing the aggregate on the top of the sieve in the order of the size of the sieve holes to screen the particle size of the aggregate, and weighing the weight of the aggregate on each layer of the sieve one by one after the screening is completed;
[0017] S13, calculating the percentage of the mass of aggregate passing through each layer of the sieve to the total mass of the aggregate, obtaining the cumulative sieve residue percentage and the pass rate, and determining the particle size distribution of the aggregate;
[0018] S14, according to the screening results, the aggregate is divided into four grades: 0~2.36mm, 2.36mm~4.75mm, 4.75~9.5mm and 9.5mm~19.5mm;
[0019] S15, setting the upper and lower limits of the gradation to control the composite gradation, and taking the median of the gradation as a reference, using the planning solution method to obtain the gradation of the four-grade aggregate, and determining the aggregate gradation.
[0020] On the basis of the above technical solution, preferably, step S2 includes the following sub-steps:
[0021] S21, determining the type of asphalt mixture, wherein the type of asphalt mixture includes asphalt, aggregate and mineral powder, the asphalt is selected from rubber powder modified asphalt, the aggregate is selected from steel slag, and the mineral powder is selected from limestone mineral powder;
[0022] S22, preset the asphalt dosage value, select multiple asphalt dosages at intervals of about 0.3%, and form multiple different Marshall standard test pieces;
[0023] S23, Marshall test was carried out on Marshall standard specimens of each bitumen dosage to determine the void ratio, mineral interstitial ratio, stability, flow value and saturation parameters;
[0024] S24, drawing a volume parameter asphalt dosage curve of each Marshall standard specimen, and obtaining an optimal asphalt dosage according to the parameter curve;
[0025] S25, rutting test, low temperature beam bending test and freeze-thaw splitting test are carried out on the asphalt mixture to verify the mix proportion of the asphalt mixture.
[0026] Based on the above technical solution, preferably, step S3 includes the following sub-steps:
[0027] S31, preparing indirect tensile test pieces of asphalt mixture and asphalt mortar, and conducting indirect tensile tests on them, and obtaining load-displacement curves of the indirect tensile tests, wherein the specimen size is a standard specimen of 100 mm×40 mm, the loading method of the indirect tensile test adopts a displacement control mode, the loading rate is 50 mm / min, the test temperature is 20°C, the asphalt mortar includes asphalt, mineral powder and fine aggregate, the maximum particle size of the fine aggregate used in the preparation of the mortar is 2.36 mm, and the optimal asphalt content of the mortar is 12.3%;
[0028] S32. Prepare dynamic modulus test specimens of asphalt mortar, conduct dynamic modulus tests on them, and obtain their dynamic modulus data. Among them, the size of the dynamic modulus test specimens is a cylindrical specimen with dimensions of 150 mm × 100 mm. The test conditions are carried out at five temperatures of -10°C, 5°C, 20°C, 35°C, and 50°C respectively, and six loading frequencies of 25 Hz, 10 Hz, 5 Hz, 1 Hz, 0.5 Hz, and 0.1 Hz are selected for each temperature;
[0029] S33. Prepare aggregate-asphalt-aggregate interface tensile test specimens, conduct interface tensile tests on them, and obtain the load-displacement curves of the interface tensile tests. Among them, the aggregate size of the aggregate-asphalt-aggregate interface tensile test specimens is a cubic specimen with dimensions of 1.5 cm × 1.5 cm × 1.5 cm. The two ends of the specimen are bonded to a rectangular polypropylene fixture using an adhesive. The test loading rate is 1 mm / min, and the test temperature is 20°C.
[0030] On the basis of the above technical solutions, preferably, step S4 includes the following sub-steps:
[0031] S41. Convert the three-dimensional gradation of the aggregate gradation of the asphalt mixture into a two-dimensional gradation. The expression is:
[0032]
[0033] In the formula, D max is the maximum aggregate size ratio; D O is the aggregate size; P k is the percentage of the aggregate in the total volume of the asphalt mixture; P (D < D0) is the probability that the aggregate with particle size D is less than D 0 ;
[0034] S42. Randomly generate finite element specimens for the indirect tensile test of asphalt mixtures with irregular aggregates in two dimensions according to the two-dimensional gradation;
[0035] S43. Insert zero-thickness cohesive elements into the finite element specimens for the indirect tensile test of asphalt mixtures with irregular aggregates, conduct mesh generation, and assign different element types to the finite element specimens for the indirect tensile test of asphalt mixtures with irregular aggregates. The element types include coarse aggregate solid elements, asphalt mortar solid elements, and Cohesive elements of asphalt mortar;
[0036] The coarse aggregate entity unit adopts a three-node linear plane stress triangle unit, the asphalt mortar entity unit adopts a four-node bilinear plane stress quadrilateral unit with reduced integration, the asphalt mortar cohesive unit adopts a four-node two-dimensional bonding unit, and a zero-thickness interface cohesive unit is used to bond the asphalt mortar and the interface between the asphalt mortar and the coarse aggregate;
[0037] S44, calibrate parameters of indirect tensile test finite element specimens of asphalt mixture with irregular aggregates based on indirect tensile tests of asphalt mortar and mixture, dynamic modulus test of asphalt mortar, and aggregate-asphalt-aggregate interface tensile test;
[0038] S45, obtain the elastic modulus of asphalt mortar and aggregate through nanoindentation test, obtain the Poisson's ratio of asphalt mortar and aggregate through universal material testing machine, determine the elastic modulus and Poisson's ratio of asphalt mortar and aggregate, set corresponding boundary conditions and apply corresponding loads to the finite element specimens according to the indirect tensile test, perform finite element simulation, and obtain finite element simulation results.
[0039] On the basis of the above technical solution, preferably, the randomly generating irregular aggregate in step S42 includes the following sub-steps:
[0040] The radius R is randomly selected within the particle size distribution range, and circular aggregate is generated with R as the radius;
[0041] A coordinate O is randomly selected inside the circular aggregate, and a two-dimensional coordinate system is established with O as the origin;
[0042] When there is at least one coordinate point in each quadrant, multiple coordinate points are selected on the circular aggregate boundary, and adjacent coordinate points are connected to generate an indirect tensile test finite element specimen of asphalt mixture with irregular aggregate.
[0043] Based on the above technical solution, preferably, step S44 includes the following sub-steps:
[0044] A bilinear constitutive model considering bond softening is constructed to calculate the tensile strength and fracture energy of the indirect tensile test of asphalt mortar and the tensile test of aggregate-asphalt-aggregate interface. The zero-thickness interface cohesive unit parameters at the interface of asphalt mortar and asphalt mortar and coarse aggregate are defined. The expression is:
[0045]
[0046] In the formula, G f is the fracture energy of asphalt mixture; W f is the work of fracture, i.e., the area enclosed by the load-displacement curve; A lig is the ligament area;P ( u ) is the load, u is displacement;
[0047] The tensile strength is calculated from the peak load of the load-displacement curve;
[0048] According to the dynamic modulus test results of asphalt mortar, the frequencies at various temperatures were converted into the corresponding reduced frequency values at 20°C. The dynamic modulus master curve was obtained by translation with the shift factor, and the viscoelastic parameters of asphalt mortar were calculated in combination with the Boltzmann constitutive relationship.
[0049] Based on the above technical solution, preferably, step S5 includes the following sub-steps:
[0050] The error range threshold is preset, the load-displacement curve results obtained by finite element simulation and indirect tensile test are compared, and the fracture energy of finite element specimen and test specimen are calculated respectively through the load-displacement curve;
[0051] The error value is calculated based on the fracture energy of the finite element specimen and the experimental specimen;
[0052] The error value is compared with the error range threshold. If the error value is within the error range threshold, the finite element simulation result is determined to be accurate, and the cracking images of crack initiation, crack propagation and crack penetration of the asphalt mixture indirect tensile test numerical specimen are output.
[0053] Based on the above technical solution, preferably, step S6 includes the following sub-steps:
[0054] S61, randomly generating circular and elliptical aggregates in two dimensions according to two-dimensional grading;
[0055] The randomly generated elliptical aggregate comprises first determining the major and minor axes of the ellipse according to the aggregate gradation, randomly selecting a point in a preset area as the center position of the ellipse, and generating elliptical aggregates with different orientations by randomly rotating the angles;
[0056] S62, establishing indirect tensile test finite element specimens of asphalt mortar-circular aggregate and asphalt mortar-elliptical aggregate interface transition zones based on randomly generated circular and elliptical aggregates, and performing finite element simulations to output crack propagation trajectories and total crack length versus finite element field output time curves of the three types of indirect tensile test finite element specimens at complete failure of the interface transition zones;
[0057] According to the variation curve of total crack length with finite element field output time, a crack length prediction model is constructed to obtain the influence of interface transition zone difference on the crack extension behavior of asphalt mixture finite element specimens. The expression is:
[0058]
[0059] In the formula, y is the crack length; x is the field output time, a, b, c are fitting parameters, k is the adjustment coefficient, B is the error value.
[0060] Based on the above technical solution, preferably, step S7 includes the following sub-steps:
[0061] S71, randomly generate indirect tensile test finite element specimens with irregular aggregates and different void ratios in two dimensions according to two-dimensional grading, and perform finite element simulation.
[0062] The load-displacement curve and energy-displacement curve of the indirect tensile test finite element specimens with different void ratios are output to obtain the effect of void ratio changes on cracking behavior. The increase in void ratio intensifies the formation and expansion of cracks in asphalt mixtures.
[0063] The method for simulating the crack propagation behavior of heterogeneous asphalt mixtures of the present invention has the following beneficial effects compared with the prior art:
[0064] (1) By setting up finite element software, a finite element model is established for the indirect tensile cracking test of asphalt mixture. The finite element model can be used to visualize and quantitatively analyze the crack initiation and propagation characteristics of asphalt mixture from multiple angles, and the influence of the interface transition zone and void ratio on the cracking behavior of asphalt mixture can be studied at the microscopic scale, thereby more accurately revealing the cracking mechanism of asphalt mixture and providing effective data support for the performance evaluation of asphalt mixture;
[0065] (2) By adopting a random aggregate generation algorithm, finite element specimens of asphalt mixture indirect tensile test with irregular aggregates are randomly generated in two dimensions. This can more realistically simulate the heterogeneity of asphalt mixture and the random distribution characteristics of aggregates in actual roads, thereby improving the accuracy of the finite element model. The reliability of the model is further verified by comparing the load-displacement curves obtained by finite element simulation and indirect tensile test.
[0066] (3) Through the constructed finite element model, the crack propagation trajectory of the aggregate interface transition zone with different shapes such as circular and elliptical shapes and the change curve of the total crack length over time are compared to quantify the influence mechanism of the interface transition zone characteristics on crack propagation. By simulating the load-displacement and energy-displacement curves under different void ratios, the influence of void ratio on the anti-cracking performance of asphalt mixture is quantified, and the performance of different asphalt mixtures can be evaluated. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0068] Figure 1 It is a flow chart of the method for simulating the crack propagation behavior of heterogeneous asphalt mixture of the present invention;
[0069] Figure 2 A schematic diagram of a cohesive unit generated by asphalt mortar and asphalt mortar-aggregate interface in the method for simulating crack propagation behavior of heterogeneous asphalt mixture of the present invention;
[0070] Figure 2 (a) is a schematic diagram of the Cohesive unit generated inside the asphalt mortar. Figure 2 (b) is a schematic diagram of the Cohesive unit generated at the asphalt mortar-aggregate interface;
[0071] Figure 3 It is a schematic diagram of the comparison results of the finite element simulation of the method for simulating the crack extension behavior of the heterogeneous asphalt mixture of the present invention and the load displacement curve of the indirect tensile test;
[0072] Figure 4 A schematic diagram of cracking images of crack initiation, crack extension and crack penetration of a finite element specimen of the method for simulating crack extension behavior of a heterogeneous asphalt mixture of the present invention;
[0073] Figure 4 (a) is a schematic diagram of the cracking image of the finite element specimen crack initiation. Figure 4 (b) is a schematic diagram of the crack image of the finite element specimen crack extension; Figure 4 (c) is a schematic diagram of the cracking image of the finite element specimen with crack penetration;
[0074] Figure 5 It is a crack propagation trajectory diagram of the three interface transition zone numerical specimens of the circular aggregate interface, the elliptical aggregate interface and the irregular aggregate interface of the method for simulating the crack propagation behavior of the heterogeneous asphalt mixture of the present invention when they fail;
[0075] Figure 5 (a) is the crack propagation trajectory diagram of the circular aggregate interface transition zone numerical specimen when it fails; Figure 5 (b) is the crack propagation trajectory diagram of the numerical specimen at the elliptical aggregate interface transition zone when it fails; Figure 5 (c) is the crack propagation trajectory diagram of the numerical specimen at the transition zone of the irregular aggregate interface when it fails;
[0076] Figure 6 A curve diagram showing the variation of the total crack length of the non-homogeneous asphalt mixture crack extension behavior simulation method according to the present invention with respect to the finite element field output time;
[0077] Figure 7 It is a load displacement curve diagram of three void ratio finite element specimens of the method for simulating the crack extension behavior of heterogeneous asphalt mixture of the present invention;
[0078] Figure 8 It is an energy displacement curve diagram of three void ratio finite element specimens of the method for simulating the crack extension behavior of heterogeneous asphalt mixture of the present invention;
[0079] Fig. 9 It is a diagram of local cracking phenomenon of finite element specimens of indirect tensile test of three interface transition zones of circular aggregate, elliptical aggregate and irregular aggregate in the method for simulating crack propagation behavior of heterogeneous asphalt mixture of the present invention;
[0080] Fig. 9 (a1) and (a2) are both diagrams of local cracking phenomena of the finite element specimens of the indirect tension test in the transition zone of the circular aggregate interface; Fig. 9 (b1) and (b2) are both diagrams of local cracking phenomena of the finite element specimens of the indirect tension test in the elliptical aggregate interface transition zone; Fig. 9 (c1) and (c2) are both local cracking phenomenon diagrams of the finite element specimens of the indirect tensile test in the transition zone of the irregular aggregate interface;
[0081] Fig.10 It is a crack extension path diagram of the indirect tensile test finite element specimens with three void ratios of 2%, 4% and 6% in the method for simulating crack extension behavior of heterogeneous asphalt mixture of the present invention;
[0082] Fig.10 (a) is the crack propagation path diagram of the finite element specimen of the indirect tensile test with a porosity of 2%; Fig.10 (b) is the crack propagation path diagram of the finite element specimen of the indirect tensile test with a porosity of 4%; Fig.10 (c) is the crack propagation path diagram of the finite element specimen of the indirect tensile test with a porosity of 6%. DETAILED DESCRIPTION
[0083] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0084] In this example, asphalt mixture is a heterogeneous material composed of coarse aggregate, asphalt mortar and voids, and the generation of its cracks usually originates from the changes in the microscopic characteristics of the structure. However, traditional mechanical properties tests cannot effectively capture the formation process of asphalt mixture cracks, and lack consideration of internal mesoscopic and microscopic mechanisms, thus hindering in-depth research on the crack propagation behavior and cracking mechanism of asphalt mixtures.
[0085] The embodiment of the present application uses finite element software to establish a finite element model for the indirect tensile cracking test of asphalt mixture. The finite element model can be used to visualize and quantitatively analyze the crack initiation and propagation characteristics of the asphalt mixture from multiple angles, and the influence of the interface transition zone and void ratio on the cracking behavior of the asphalt mixture can be studied at a mesoscopic scale.
[0086] The present embodiment is described in detail:
[0087] like Figure 1-10 As shown, a method for simulating crack propagation behavior of a heterogeneous asphalt mixture of the present invention comprises the following steps:
[0088] S1, use screening test to obtain the aggregate particle size distribution, and determine the aggregate gradation based on the screening results.
[0089] Step S1 includes the following sub-steps:
[0090] S11, placing the aggregate into an oven, drying to constant weight, and selecting the mesh size of the sieve according to the aggregate size;
[0091] S12, placing the aggregate on the top of the sieve in the order of the size of the sieve holes to screen the particle size of the aggregate, and weighing the weight of the aggregate on each layer of the sieve one by one after the screening is completed;
[0092] S13, calculate the percentage of the mass of aggregate passing through each layer of sieve to the total mass of aggregate, obtain the cumulative screen residue percentage and pass rate, and determine the particle size distribution of aggregate; as shown in Table 1, Table 1 is the particle size distribution data of AC-16 mineral composition design;
[0093] Table 1
[0094]
[0095] S14, according to the screening results, the aggregate is divided into four grades: 0~2.36mm, 2.36mm~4.75mm, 4.75~9.5mm and 9.5mm~19.5mm;
[0096] S15, setting the upper and lower limits of the gradation to control the composite gradation, and taking the median of the gradation as a reference, using the planning solution method to obtain the gradation of the four-grade aggregate, and determining the aggregate gradation.
[0097] S2, determining the type of asphalt mixture, conducting tests based on aggregate gradation and the type of asphalt mixture to obtain the optimal asphalt dosage, wherein the type of asphalt mixture includes asphalt, aggregate and mineral powder.
[0098] Step S2 includes the following sub-steps:
[0099] S21, determining the type of asphalt mixture, wherein the type of asphalt mixture includes asphalt, aggregate and mineral powder, the asphalt is selected from rubber powder modified asphalt, the aggregate is selected from steel slag, and the mineral powder is selected from limestone mineral powder;
[0100] S22, preset the asphalt dosage value, select multiple asphalt dosages at intervals of about 0.3%, and form multiple different Marshall standard test pieces;
[0101] S23, Marshall test was carried out on Marshall standard specimens of each bitumen dosage to determine the void ratio, mineral interstitial ratio, stability, flow value and saturation parameters;
[0102] S24, drawing a volume parameter asphalt dosage curve of each Marshall standard specimen, and obtaining an optimal asphalt dosage according to the parameter curve;
[0103] S25, rutting test, low temperature beam bending test and freeze-thaw splitting test are carried out on the asphalt mixture to verify the mix proportion of the asphalt mixture.
[0104] Specifically, an asphalt dosage is estimated, and five different optimal asphalt dosages are formed into Marshall standard specimens at intervals of 0.3%. The influence of different asphalt dosages on the performance of the mixture can be examined. Marshall tests are carried out on Marshall standard specimens with each asphalt dosage to measure the void ratio, mineral gap ratio, stability, flow value and saturation parameters. These parameters can comprehensively reflect the mechanical properties, durability and stability of the mixture. The volume parameter asphalt dosage curve of each Marshall standard specimen is drawn, and the optimal asphalt dosage is intuitively obtained through the parameter curve. The optimal asphalt dosage of the asphalt mixture is determined to be 5.6% through the Marshall test method. The asphalt mixture is subjected to rutting tests, low-temperature beam bending tests and freeze-thaw splitting tests to verify whether the above mix ratio results are reasonable and ensure that excellent pavement performance can be provided in actual construction. The test results are shown in Table 2. Table 2 is the asphalt mixture performance verification results.
[0105] Table 2
[0106]
[0107] In this embodiment, by accurately determining the optimal asphalt dosage and optimizing the asphalt mixture ratio, the quality stability and uniformity of the asphalt mixture are improved, which helps to reduce quality fluctuations and defect rates during the construction process and improve the overall project quality. At the same time, the optimized asphalt mixture ratio can reduce unnecessary material waste and maintenance costs.
[0108] S3, preparing indirect tensile test pieces of asphalt mixture and asphalt mortar, dynamic modulus test pieces of asphalt mortar and aggregate-asphalt-aggregate interface tensile test pieces, performing corresponding indoor test tests on each test piece, and obtaining corresponding test results;
[0109] Step S3 includes the following sub-steps:
[0110] S31, preparing indirect tensile test pieces of asphalt mixture and asphalt mortar, and conducting indirect tensile tests on them, and obtaining load-displacement curves of the indirect tensile tests, wherein the specimen size is a standard specimen of 100 mm×40 mm, the loading method of the indirect tensile test adopts a displacement control mode, the loading rate is 50 mm / min, the test temperature is 20°C, the asphalt mortar includes asphalt, mineral powder and fine aggregate, the maximum particle size of the fine aggregate used in the preparation of the mortar is 2.36 mm, and the optimal asphalt content of the mortar is 12.3%;
[0111] S32, preparing a dynamic modulus test piece of asphalt mortar, and conducting a dynamic modulus test on it to obtain its dynamic modulus data, wherein the dynamic modulus test piece is a cylindrical test piece of 150 mm×100 mm in size, and the test conditions are respectively carried out at five temperatures of -10°C, 5°C, 20°C, 35°C and 50°C, and six loading frequencies of 25 Hz, 10 Hz, 5 Hz, 1 Hz, 0.5 Hz and 0.1 Hz are selected for each temperature;
[0112] S33, prepare aggregate-asphalt-aggregate interface tensile test pieces, and conduct interface tensile test on them to obtain the load-displacement curve of the interface tensile test, wherein the aggregate size of the aggregate-asphalt-aggregate interface tensile test piece is a cubic specimen of 1.5cm×1.5cm×1.5cm, and both ends of the specimen are bonded to a rectangular polypropylene clamp with an adhesive, the test loading rate is 1mm / min, and the test temperature is 20°C.
[0113] S4, converting the three-dimensional gradation of the aggregate gradation of the asphalt mixture into a two-dimensional gradation, randomly generating an indirect tensile test finite element specimen of the asphalt mixture with irregular aggregates in a two-dimensional dimension according to the two-dimensional gradation, and performing a finite element simulation to obtain a finite element simulation result;
[0114] Step S4 includes the following sub-steps:
[0115] S41. Convert the three-dimensional gradation of the aggregate gradation of the asphalt mixture into a two-dimensional gradation. The expression is:
[0116]
[0117] In the formula, D max is the maximum aggregate size; D O is the aggregate size; P k is the percentage of the aggregate in the total volume of the asphalt mixture; P (D < D0) means the probability that the aggregate with particle size D is less than D 0 ;
[0118] S42. Randomly generate a finite element specimen for the indirect tensile test of the asphalt mixture with irregular aggregates in two dimensions according to the two-dimensional gradation.
[0119] In this embodiment, write a Python language for generating random aggregates using a Python program and save it as a.py file. Then, create a part with a diameter of 100 mm under the part function module in the Abaqus finite element software. Finally, run the.py file for generating random aggregates in the Abaqus finite element software to generate a finite element specimen for the indirect tensile test of the asphalt mixture with irregular aggregates in the part with a diameter of 100 mm.
[0120] Among them, the randomly generating irregular aggregates in step S42 includes the following sub-steps:
[0121] Randomly select a radius R within the particle size distribution range and generate a circular aggregate with radius R;
[0122] Randomly select a coordinate O inside the circular aggregate and establish a two-dimensional coordinate system with O as the origin;
[0123] When there is at least one coordinate point in each quadrant, select multiple coordinate points on the boundary of the circular aggregate and connect the adjacent coordinate points to generate a finite element specimen for the indirect tensile test of the asphalt mixture with irregular aggregates;
[0124] S43. Insert a zero-thickness cohesive unit into the finite element specimen for the indirect tensile test of the asphalt mixture with irregular aggregates, and perform mesh division. Assign different element types to the finite element specimen for the indirect tensile test of the asphalt mixture with irregular aggregates. The element types include coarse aggregate solid elements, asphalt mortar solid elements, and Cohesive elements of asphalt mortar;
[0125] In this embodiment, a Python program is used to write the Python language for batch inserting zero-thickness cohesive units and save it as a .py file. The finite element software is used to mesh the finite element specimens of the indirect tensile test of asphalt mixture with irregular aggregate. The .py file for batch inserting zero-thickness cohesive units is run in the finite element software to generate a set of cohesive units at the asphalt mortar and the asphalt mortar-aggregate interface.
[0126] The coarse aggregate entity unit adopts a three-node linear plane stress triangle unit, the asphalt mortar entity unit adopts a four-node bilinear plane stress quadrilateral unit with reduced integration, the asphalt mortar cohesive unit adopts a four-node two-dimensional bonding unit, and a zero-thickness interface cohesive unit is used to bond the asphalt mortar and the interface between the asphalt mortar and the coarse aggregate;
[0127] S44, calibrate parameters of indirect tensile test finite element specimens of asphalt mixture with irregular aggregates based on indirect tensile tests of asphalt mortar and mixture, dynamic modulus test of asphalt mortar, and aggregate-asphalt-aggregate interface tensile test;
[0128] Wherein, step S44 includes the following sub-steps:
[0129] A bilinear constitutive model considering bond softening is constructed to calculate the tensile strength and fracture energy of the indirect tensile test of asphalt mortar and the tensile test of aggregate-asphalt-aggregate interface. The zero-thickness interface cohesive unit parameters at the interface of asphalt mortar and asphalt mortar and coarse aggregate are defined. The expression is:
[0130]
[0131] In the formula, G f is the fracture energy of asphalt mixture; W f is the work of fracture, i.e., the area enclosed by the load-displacement curve; A lig is the ligament area; P ( u ) is the load, u is displacement;
[0132] The tensile strength is calculated from the peak load of the load-displacement curve using the expression:
[0133] σ t = P max / A lig
[0134] In the formula, σ t is the tensile strength,P max is the peak load, A lig is the ligament area.
[0135] According to the dynamic modulus test results of asphalt mortar, the frequencies at various temperatures were converted into the corresponding reduced frequency values at 20°C, and the dynamic modulus master curve was obtained by translation with the shift factor. The viscoelastic parameters of asphalt mortar were calculated in combination with the Boltzmann constitutive relationship.
[0136] S45, obtain the elastic modulus of asphalt mortar and aggregate through nanoindentation test, obtain the Poisson's ratio of asphalt mortar and aggregate through universal material testing machine, determine the elastic modulus and Poisson's ratio of asphalt mortar and aggregate, set corresponding boundary conditions and apply corresponding loads to the finite element specimens according to the indirect tensile test, perform finite element simulation, and obtain finite element simulation results.
[0137] Specifically, the viscoelastic parameters of asphalt mortar are shown in Table 3, and other parameters of Cohesive unit and model are shown in Table 4;
[0138] Table 3
[0139]
[0140] Table 4
[0141]
[0142] The boundary conditions in this embodiment are horizontal, vertical and rotational. In order to keep the test consistent, a reference point is set at the center of the bottom strip of the finite element specimen according to the indirect tensile test, and the reference point is fixed to fix the relevant nodes, thereby limiting the horizontal, vertical and rotational degrees of freedom of the bottom strip. The software is set to U1=U2=UR3=0. At the same time, a reference point is set at the center of the top strip, and a vertical displacement is applied to the reference point at a rate of 0.83mm / s.
[0143] It should be noted that by converting the three-dimensional gradation into a two-dimensional gradation, the complexity of the model is simplified while retaining key information, making the simulation process more efficient. The Python program is used to randomly generate irregular aggregates to simulate the diversity and randomness of aggregates in real asphalt mixtures. The introduction of irregular aggregates improves the accuracy and authenticity of the simulation results, which helps to have a deeper understanding of the mechanical behavior of asphalt mixtures. The asphalt mixture specimens with irregular aggregates are refined to ensure the accuracy of the simulation results. Different types of units are used to simulate the mechanical behavior of different parts to improve the accuracy of the model. The finite element specimens are calibrated through indirect tensile tests, dynamic modulus tests and interface tensile tests to ensure the accuracy of the simulation parameters. The dynamic modulus master curve is obtained by translation using the Boltzmann constitutive relationship and the shift factor. The influence of temperature on the viscoelastic parameters of asphalt mortar is considered to improve the reliability of the simulation results.
[0144] S5, compare the finite element simulation results with the corresponding test results to verify whether the finite element simulation results are accurate, and output the cracking diagrams of crack initiation, crack propagation and crack penetration of the asphalt mixture indirect tensile test numerical specimen.
[0145] Wherein, step S5 includes the following sub-steps:
[0146] The error range threshold is preset, the load-displacement curve results obtained by finite element simulation and indirect tensile test are compared, and the fracture energy of finite element specimen and test specimen are calculated respectively through the load-displacement curve;
[0147] The error value is calculated based on the fracture energy of the finite element specimen and the experimental specimen;
[0148] The error value is compared with the error range threshold. If the error value is within the error range threshold, the finite element simulation result is determined to be accurate, and the cracking images of crack initiation, crack propagation and crack penetration of the asphalt mixture indirect tensile test numerical specimen are output.
[0149] Specifically, the error range threshold is 5%. The load-displacement curve results obtained by finite element simulation and indirect tensile test are compared, and the fracture energy of finite element specimens and test specimens is calculated by load-displacement curve to judge the accuracy of simulation results. The comparison results of load-displacement curve are as follows: Figure 3 As shown, the fracture energy results are shown in Table 5;
[0150] Table 5
[0151]
[0152] according to Figure 3It can be seen that the load-displacement curves obtained from the test and the finite element simulation follow similar development laws. At the same time, it can be seen from Table 5 that the error between the fracture energy index calculated from the finite element simulation and the indoor test results is less than 5%, which proves that the established finite element model has high reliability.
[0153] The finite element software can be used to output the crack initiation, crack extension and crack penetration images of the finite element indirect tensile test of asphalt mixture, and the crack extension process can be analyzed. Figure 4 shown.
[0154] S6, establish indirect tensile test finite element specimens of asphalt mortar-circular and elliptical aggregate interface transition zones, and perform finite element simulations to output the crack propagation trajectory and the curve of total crack length changing with finite element field output time when the three types of indirect tensile test finite element specimens of interface transition zones completely fail, and obtain the influence of interface transition zone differences on crack propagation behavior;
[0155] Step S6 includes the following sub-steps:
[0156] S61, randomly generating circular and elliptical aggregates in two dimensions according to two-dimensional grading;
[0157] The randomly generated elliptical aggregate comprises first determining the major and minor axes of the ellipse according to the aggregate gradation, randomly selecting a point in a preset area as the center position of the ellipse, and generating elliptical aggregates with different orientations by randomly rotating the angles;
[0158] S62, establishing indirect tensile test finite element specimens of asphalt mortar-circular aggregate and asphalt mortar-elliptical aggregate interface transition zones based on randomly generated circular and elliptical aggregates, and performing finite element simulations to output crack propagation trajectories and total crack length versus finite element field output time curves of the three types of indirect tensile test finite element specimens at complete failure of the interface transition zones;
[0159] According to the variation curve of total crack length with finite element field output time, a crack length prediction model is constructed to obtain the influence of interface transition zone difference on the crack extension behavior of asphalt mixture finite element specimens. The expression is:
[0160]
[0161] In the formula, y is the crack length; x is the field output time, a, b, c are fitting parameters, k is the adjustment coefficient, B is the error value.
[0162] It should be noted that in the process of generating elliptical aggregates, it is also necessary to check whether the generated elliptical aggregates meet the expected distribution and characteristics, and adjust them as needed. The crack extension trajectory of the three interface transition zone indirect tensile test finite element specimens when they completely fail and the curve of the total crack length changing with the finite element field output time are output to quantitatively analyze the influence of the interface transition zone difference on the crack extension behavior of the asphalt mixture numerical specimen. The crack extension trajectory is as follows: Figure 5 As shown in the figure, the variation curve of total crack length with finite element field output time is as follows: Figure 6 shown.
[0163] S7, establish indirect tensile test finite element specimens with different void ratios, perform finite element simulation, output load-displacement and energy-displacement curves of the indirect tensile test finite element specimens with different void ratios, and obtain the influence of void ratio change on cracking behavior.
[0164] Step S7 includes the following sub-steps:
[0165] S71, randomly generate indirect tensile test finite element specimens with irregular aggregates and different void ratios in two dimensions according to two-dimensional grading, and perform finite element simulation;
[0166] The load-displacement curve and energy-displacement curve of the indirect tensile test finite element specimens with different void ratios are output to obtain the effect of void ratio changes on cracking behavior. The increase in void ratio intensifies the formation and expansion of cracks in asphalt mixtures.
[0167] Specifically, a Python program was used to write a Python language with irregular aggregates and voids of 2%, 4% and 6% of the whole specimen, and the code was saved as a .py file. A component with a diameter of 100 mm was created under the part function module in the finite element software. The .py file was run in the finite element software to generate finite element specimens with irregular aggregates and voids. The load-displacement and energy-displacement curves of the indirect tensile test numerical specimens with three void ratios were output. The influence of the change in void ratio on the cracking behavior of the asphalt mixture numerical specimens was analyzed. The load-displacement and energy-displacement curves are shown in Figure 2. Figure 7 and Figure 8 As shown;
[0168] Depend on Figure 7 and Figure 8 It can be seen that compared with the numerical specimen with a void ratio of 2%, the peak loads of the numerical specimens with a void ratio of 4% and 6% decreased by 403.8N and 866.7N respectively; the failure displacements decreased by 0.26mm and 0.37mm respectively; the energy consumed in failure decreased by 26.6mJ and 54.6mJ respectively, which means that the increase in void ratio will aggravate the formation and expansion of cracks in asphalt mixtures to a certain extent, increase the possibility of cracking and damage to the specimens, and thus weaken their anti-cracking performance.
[0169] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for simulating crack propagation behavior of heterogeneous asphalt mixture, characterized in that: The following steps are involved: S1, use screening test to obtain the aggregate particle size distribution, and determine the aggregate gradation based on the screening results; S2, determining the type of asphalt mixture, conducting tests according to aggregate gradation and the type of asphalt mixture to obtain an optimal asphalt dosage, wherein the type of asphalt mixture includes asphalt, aggregate and mineral powder; S3, preparing indirect tensile test pieces of asphalt mixture and asphalt mortar, dynamic modulus test pieces of asphalt mortar and aggregate-asphalt-aggregate interface tensile test pieces, performing corresponding indoor test tests on each test piece, and obtaining corresponding test results; S4, converting the three-dimensional gradation of the aggregate gradation of the asphalt mixture into a two-dimensional gradation, randomly generating an indirect tensile test finite element specimen of the asphalt mixture with irregular aggregates in a two-dimensional dimension according to the two-dimensional gradation, and performing a finite element simulation to obtain a finite element simulation result; S5, comparing the finite element simulation results with the corresponding test results to verify whether the finite element simulation results are accurate, and outputting cracking images of crack initiation, crack propagation and crack penetration of the asphalt mixture indirect tensile test numerical specimen; S6, establish indirect tensile test finite element specimens of asphalt mortar-circular and elliptical aggregate interface transition zones, and perform finite element simulations to output the crack propagation trajectory and the curve of total crack length changing with finite element field output time when the three types of indirect tensile test finite element specimens of interface transition zones completely fail, and obtain the influence of interface transition zone differences on crack propagation behavior; S7, establish indirect tensile test finite element specimens with different void ratios, perform finite element simulation, output load-displacement and energy-displacement curves of the indirect tensile test finite element specimens with different void ratios, and obtain the influence of void ratio change on cracking behavior.
2. The method for simulating crack propagation behavior of heterogeneous asphalt mixture according to claim 1, characterized in that: The step S1 of obtaining the particle size distribution of aggregate by a screening test and determining the aggregate gradation according to the screening result includes the following sub-steps: S11, placing the aggregate into an oven, drying to constant weight, and selecting the mesh size of the sieve according to the aggregate size; S12, placing the aggregate on the top of the sieve in the order of the size of the sieve holes to screen the particle size of the aggregate, and weighing the weight of the aggregate on each layer of the sieve one by one after the screening is completed; S13, calculating the percentage of the mass of aggregate passing through each layer of the sieve to the total mass of the aggregate, obtaining the cumulative sieve residue percentage and the pass rate, and determining the particle size distribution of the aggregate; S14, according to the screening results, the aggregate is divided into four grades: 0~2.36mm, 2.36mm~4.75mm, 4.75~9.5mm and 9.5mm~19.5mm; S15, setting the upper and lower limits of the gradation to control the composite gradation, and taking the median of the gradation as a reference, using the planning solution method to obtain the gradation of the four-grade aggregate, and determining the aggregate gradation.
3. The method for simulating crack propagation behavior of heterogeneous asphalt mixture according to claim 2, characterized in that: Step S2 includes the following sub-steps: S21, determining the type of asphalt mixture, wherein the type of asphalt mixture includes asphalt, aggregate and mineral powder, the asphalt is selected from rubber powder modified asphalt, the aggregate is selected from steel slag, and the mineral powder is selected from limestone mineral powder; S22, preset the asphalt dosage value, select multiple asphalt dosages at intervals of about 0.3%, and form multiple different Marshall standard test pieces; S23, Marshall test was carried out on Marshall standard specimens of each bitumen dosage to determine the void ratio, mineral interstitial ratio, stability, flow value and saturation parameters; S24, drawing a volume parameter asphalt dosage curve of each Marshall standard specimen, and obtaining an optimal asphalt dosage according to the parameter curve; S25, rutting test, low temperature beam bending test and freeze-thaw splitting test are carried out on the asphalt mixture to verify the mix proportion of the asphalt mixture.
4. The method for simulating crack propagation behavior of heterogeneous asphalt mixture according to claim 3, characterized in that: Step S3 includes the following sub-steps: S31, preparing indirect tensile test pieces of asphalt mixture and asphalt mortar, and conducting indirect tensile tests on them, and obtaining load-displacement curves of the indirect tensile tests, wherein the specimen size is a standard specimen of 100 mm×40 mm, the loading method of the indirect tensile test adopts a displacement control mode, the loading rate is 50 mm / min, the test temperature is 20°C, the asphalt mortar includes asphalt, mineral powder and fine aggregate, the maximum particle size of the fine aggregate used in the preparation of the mortar is 2.36 mm, and the optimal asphalt content of the mortar is 12.3%; S32, preparing a dynamic modulus test piece of asphalt mortar, and conducting a dynamic modulus test on it to obtain its dynamic modulus data, wherein the dynamic modulus test piece is a cylindrical test piece of 150 mm×100 mm in size, and the test conditions are respectively carried out at five temperatures of -10°C, 5°C, 20°C, 35°C and 50°C, and six loading frequencies of 25 Hz, 10 Hz, 5 Hz, 1 Hz, 0.5 Hz and 0.1 Hz are selected for each temperature; S33, prepare aggregate-asphalt-aggregate interface tensile test pieces, and conduct interface tensile test on them to obtain the load-displacement curve of the interface tensile test, wherein the aggregate size of the aggregate-asphalt-aggregate interface tensile test piece is a cubic specimen of 1.5cm×1.5cm×1.5cm, and both ends of the specimen are bonded to a rectangular polypropylene clamp with an adhesive, the test loading rate is 1mm / min, and the test temperature is 20°C.
5. The method for simulating crack propagation behavior of heterogeneous asphalt mixture according to claim 4, characterized in that: Step S4 includes the following sub-steps: S41, the three-dimensional gradation of aggregate gradation of asphalt mixture is converted into two-dimensional gradation, the expression is: ; In the formula, D max is the maximum aggregate size ratio; D O is the aggregate size; P k is the percentage of the aggregate in the total volume of the asphalt mixture; P (D < D0) is the probability that the aggregate with particle size D is less than D 0 ; S42, finite element specimens of indirect tensile tests of asphalt mixtures with irregular aggregates randomly generated in two dimensions according to two-dimensional grading; S43, inserting a zero-thickness cohesion unit into the finite element specimen of the indirect tensile test of the asphalt mixture with irregular aggregate, and performing mesh division, and assigning different unit types to the finite element specimen of the indirect tensile test of the asphalt mixture with irregular aggregate, wherein the unit types include a coarse aggregate solid unit, an asphalt mortar solid unit, and a cohesive unit of the asphalt mortar; The coarse aggregate entity unit adopts a three-node linear plane stress triangle unit, the asphalt mortar entity unit adopts a four-node bilinear plane stress quadrilateral unit with reduced integration, the asphalt mortar cohesive unit adopts a four-node two-dimensional bonding unit, and a zero-thickness interface cohesive unit is used to bond the asphalt mortar and the interface between the asphalt mortar and the coarse aggregate; S44, calibrate parameters of indirect tensile test finite element specimens of asphalt mixture with irregular aggregates based on indirect tensile tests of asphalt mortar and mixture, dynamic modulus test of asphalt mortar, and aggregate-asphalt-aggregate interface tensile test; S45, obtain the elastic modulus of asphalt mortar and aggregate through nanoindentation test, obtain the Poisson's ratio of asphalt mortar and aggregate through universal material testing machine, determine the elastic modulus and Poisson's ratio of asphalt mortar and aggregate, set corresponding boundary conditions and apply corresponding loads to the finite element specimens according to the indirect tensile test, perform finite element simulation, and obtain finite element simulation results.
6. The method for simulating crack propagation behavior of heterogeneous asphalt mixture according to claim 5, characterized in that: The random generation of irregular aggregates in step S42 includes the following sub-steps: The radius R is randomly selected within the particle size distribution range, and circular aggregate is generated with R as the radius; A coordinate O is randomly selected inside the circular aggregate, and a two-dimensional coordinate system is established with O as the origin; When there is at least one coordinate point in each quadrant, multiple coordinate points are selected on the circular aggregate boundary, and adjacent coordinate points are connected to generate an indirect tensile test finite element specimen of asphalt mixture with irregular aggregate.
7. The method for simulating crack propagation behavior of heterogeneous asphalt mixture according to claim 6, characterized in that: Step S44 includes the following sub-steps: A bilinear constitutive model considering bond softening is constructed to calculate the tensile strength and fracture energy of the indirect tensile test of asphalt mortar and the tensile test of aggregate-asphalt-aggregate interface. The zero-thickness interface cohesive unit parameters at the interface of asphalt mortar and asphalt mortar and coarse aggregate are defined. The expression is: ; In the formula, G f is the fracture energy of asphalt mixture; W f is the work of fracture, i.e., the area enclosed by the load-displacement curve; A lig is the ligament area; P ( u ) is the load, u is displacement; The tensile strength is calculated from the peak load of the load-displacement curve; According to the dynamic modulus test results of asphalt mortar, the frequencies at various temperatures were converted into the corresponding reduced frequency values at 20°C. The dynamic modulus master curve was obtained by translation with the shift factor, and the viscoelastic parameters of asphalt mortar were calculated in combination with the Boltzmann constitutive relationship.
8. The method for simulating crack propagation behavior of heterogeneous asphalt mixture according to claim 7, characterized in that: Step S5 includes the following sub-steps: The error range threshold is preset, the load-displacement curve results obtained by finite element simulation and indirect tensile test are compared, and the fracture energy of finite element specimen and test specimen are calculated respectively through the load-displacement curve; The error value is calculated based on the fracture energy of the finite element specimen and the experimental specimen; The error value is compared with the error range threshold. If the error value is within the error range threshold, the finite element simulation result is determined to be accurate, and the cracking images of crack initiation, crack propagation and crack penetration of the asphalt mixture indirect tensile test numerical specimen are output.
9. The method for simulating crack propagation behavior of heterogeneous asphalt mixture according to claim 8, characterized in that: Step S6 includes the following sub-steps: S61, randomly generating circular and elliptical aggregates in two dimensions according to two-dimensional grading; The randomly generated elliptical aggregate comprises first determining the major and minor axes of the ellipse according to the aggregate gradation, randomly selecting a point in a preset area as the center position of the ellipse, and generating elliptical aggregates with different orientations by randomly rotating the angles; S62, establishing indirect tensile test finite element specimens of asphalt mortar-circular aggregate and asphalt mortar-elliptical aggregate interface transition zones based on randomly generated circular and elliptical aggregates, and performing finite element simulations to output crack propagation trajectories and total crack length versus finite element field output time curves of the three types of indirect tensile test finite element specimens at complete failure of the interface transition zones; According to the variation curve of total crack length with finite element field output time, a crack length prediction model is constructed to obtain the influence of interface transition zone difference on the crack extension behavior of asphalt mixture finite element specimens. The expression is: ; In the formula, y is the crack length; x is the field output time, a, b, c are fitting parameters, k is the adjustment coefficient, B is the error value.
10. The method for simulating crack propagation behavior of heterogeneous asphalt mixture according to claim 9, characterized in that: Step S7 includes the following sub-steps: S71, randomly generate indirect tensile test finite element specimens with irregular aggregates and different void ratios in two dimensions according to two-dimensional grading, and perform finite element simulation; The load-displacement curve and energy-displacement curve of the indirect tensile test finite element specimens with different void ratios are output to obtain the effect of void ratio changes on cracking behavior. The increase in void ratio intensifies the formation and expansion of cracks in asphalt mixtures.
Citation Information
Patent Citations
A method for simulating cracking behavior of asphalt mixture considering random inhomogeneity of binder
CN115060749B
Asphalt mixture fatigue test numerical simulation method based on random generation
CN106126820A
Asphalt pavement semi-rigid base crack monitoring method based on intelligent perception
CN116296804A